Hybrids as mirrors of the past: genomic footprints reveal spatio-temporal dynamics and extinction risk of alpine extremophytes in the mountains of Central Asia - Wróbel, Anna; Klichowska, Ewelina; Nobis, Marcin (Frontiers in Plant Science, 2024)
Hybridization is one of the key processes shaping lineage diversification, particularly in regions that experienced strong climate oscillations. The alpine biome with its rich history of glacial-interglacial cycles and complex patterns of species distribution shifts offers an excellent system to investigate the impact of gene flow on population dynamics and speciation, important issues for evolutionary biology and biodiversity conservation. In this study, we combined genomic data (DArTseq), chloroplast markers, and morphology to examine phylogenetic relationships and the permeability of species boundaries and their evolutionary outcomes among the alpine extremophilic species of Puccinellia (Poaceae) in the Pamir Mountains, a part of the Mountains of Central Asia biodiversity hotspot. We determined the occurrence of interspecific hybrids between P. himalaica and P. pamirica, which demonstrated almost symmetric ancestry from their parental species and did not show signals of introgression. According to our integrative revision, the natural hybrids between P. himalaica and P. pamirica should be classified as Puccinellia ×vachanica (pro species). Using approximate Bayesian computation for population history inference, we uncovered that P. himalaica hybridized with P. pamirica independently in multiple localities over the Holocene. Hybrids inherited the fine-scale genetic structure from their parental species, which developed these patterns earlier, during the Late Pleistocene. Hybridization had different consequences for the involved parental lineages, likely playing an important role in a continuing decline of P. himalaica in the Pamir Mountains over the Holocene. Our results show that P. himalaica should be considered a critically endangered species in the Pamir Mountains and could also be retreating across its entire range of distribution in High Mountain Asia. Using a comparative phylogeographic framework, we revealed the risk of extinction of a cold-adapted alpine species in a global biodiversity hotspot. This study highlights that genomics could unravel diversity trends under climate change and provides valuable evidence for conservation management.